Effect of LPG Content on the Performance and Emissions of A Diesel-LPG Dual-Fuel Engine (Bangladesh Journal of Scientific and Industrial Research, 2011)
In the present work, LPG, a by-product of petroleum refining process is used to replace conventional diesel fuel, partially, for improved combustion efficiency and clean burning. A conventional diesel engine was operated on the dual-fuel mode, using LPG as the primary fuel and diesel as the pilot fuel. A four-stroke, single-cylinder diesel engine, most widely used in agricultural sector, has been considered for the purpose of experimentation. The engine was operated at a constant speed of 1500 rpm at a low engine load of 20% and a high engine load of 80%. Under both these operating conditions, combustion, performance and emission characteristics of the engine have been evaluated and compared with that of baseline diesel fuel operation. At 20 % engine load the brake thermal efficiency of the engine has found to decrease with an increase in the LPG content. On the other hand at 80% engine load, it has increased with an increase in the LPG content. Same trend has been observed with regard to the mechanical efficiency. The volumetric efficiency has decreased with an increase in the LPG content at both the loads. The engine operation is more economical on dual-fuel operation at 80% engine load, whereas at 20% engine load, diesel fuel operation is found to be better. With regard to emissions, smoke density and emissions of NOx were found to reduce with an increase in LPG content at both the loads; however, emissions of HC and CO have shown the reverse trend. Key words: Dual-Fuel; LPG; Diesel; Combustion; Performance; Emissions Load. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8186 Bangladesh J. Sci. Ind. Res. 46(2), 195-200, 2011